Marine Bioresource Development – Stakeholder’s Challenges, Implementable Actions, and Business Models - Collins, Jane Eva; Vanagt, Thomas; Huys, Isabelle; Vieira, Helena (Frontiers in Marine Science, 2020)
Growth of the Blue Bioeconomy has potential for contributing positively towards economic growth, societal needs and multiple United Nations Sustainable Development Goals. However, organisations currently experience many challenges which limit success in this field. The aim of this paper is to identify trends in challenges linked to target end markets, stages in the value chain and organisation types, to suggest potential solutions and link these to potential novel business models. A survey was completed by 58 organisations representing countries across four continents, and interviews were conducted with seven selected European start-ups/ SMEs, to gather information regarding existing bottlenecks and to validate their business model. Results indicate that organisations targeting the pharmaceutical and nutraceutical sector experience a majority of challenges related to supply and technology, whereas organisations targeting the industrial biotechnology or agricultural industry experience more issues linked to market. Both bottom-up and top-down approaches could be applied in order to implement suggested actions. Analysis of the business model canvas used by start-ups/ SMEs revealed potential for improvement. In particular, it was noted that review of the ‘revenue stream’ segment within the business model, specifically regarding alternatives to governmental funding, could be helpful for the long-term survival of these types of organisations.